The use of technology to guarantee the correct dose of medicines in a hospital in agreste pernambucano - Silva Bezerra de Sousa, Thamiris; Jucelia de França, Juciara; Ribeiro de Moura, Thaís; de Vidal Neves, Hugo Leonardo (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Introduction: The health care process is one of many atribuitions to the pharmacy at the hospital. This function has the priority to assure the correct use of the the drug according with the prescription, dosage, validation and others as well are checked. Therefore the best way to garante and minimize the erros is the process of unitization. Objetives: Demonstrate one of the strategies adopted in a private hospital, highlighting the use of technology as a contributing factor combined with reducing waste and evasion of liquid medicines, verifying the benefits after implementing the equipment in the service, ensuring economic and care efficiency. Methods: The oral liquid consuption report was used to check medicines consuption before and after, issued through our ERP system, the MV Soul, between the months of December 2022 and January 2023 from Hospital Unimed Caruaru- Pernambuco. For the study, we choosed four medicines witch follow the samen rules and program that the others, with the same analysis and comparison of prescribed versus prescribed medicines. Data processing was done using graphs. Results: Using the MK5 liquid unitizing machine, there was a significant reduction of 5.57% in the total consumption of bottles, less divergence in stock and greater product traceability. Conclusion: It is concluded that, with the implementation of the service, there were improvements in the care aspect and patient safety, as it contributed to the precision of the doses dispensed and administered, thus contingency spending was carried out in a more balanced way.